The Action of 2-Aminoethyldiphenyl Borinate on the Pulmonary Arterial Hypertension and Remodeling of High-Altitude Hypoxemic Lambs - Castillo-Galan, Sebastian; Parrau, Daniela; Hernandez, Ismael; Quezada, Sebastian; Diaz, Marcela; Ebensperger, German; Herrera, Emilio A.; Moraga, Fernando A.; Iturriaga, Rodrigo; Llanos, Anibal J.; Reyes, Roberto V. (My University, 2022)
Calcium signaling is key for the contraction, differentiation, and proliferation of pulmonary arterial smooth muscle cells. Furthermore, calcium influx through store-operated channels (SOCs) is particularly important in the vasoconstrictor response to hypoxia. Previously, we found a decrease in pulmonary hypertension and remodeling in normoxic newborn lambs partially gestated under chronic hypoxia, when treated with 2-aminoethyldiphenyl borinate (2-APB), a non-specific SOC blocker. However, the effects of 2-APB are unknown in neonates completely gestated, born, and raised under environmental hypoxia. Accordingly, we studied the effects of 2-APB-treatment on the cardiopulmonary variables in lambs under chronic hypobaric hypoxia. Experiments were done in nine newborn lambs gestated, born, and raised in high altitude (3,600 m): five animals were treated with 2-APB [intravenous (i.v.) 10 mg kg(-1)] for 10 days, while other four animals received vehicle. During the treatment, cardiopulmonary variables were measured daily, and these were also evaluated during an acute episode of superimposed hypoxia, 1 day after the end of the treatment. Furthermore, pulmonary vascular remodeling was assessed by histological analysis 2 days after the end of the treatment. Basal cardiac output and mean systemic arterial pressure (SAP) and resistance from 2-APB- and vehicle-treated lambs did not differ along with the treatment. Mean pulmonary arterial pressure (mPAP) decreased after the first day of 2-APB treatment and remained lower than the vehicle-treated group until the third day, and during the fifth, sixth, and ninth day of treatment. The net mPAP increase in response to acute hypoxia did not change, but the pressure area under the curve (AUC) during hypoxia was slightly lower in 2-APB-treated lambs than in vehicle-treated lambs. Moreover, the 2-APB treatment decreased the pulmonary arterial wall thickness and the alpha-actin immunoreactivity and increased the luminal area with no changes in the vascular density. Our findings show that 2-APB treatment partially reduced the contractile hypoxic response and reverted the pulmonary vascular remodeling, but this is not enough to normalize the pulmonary hemodynamics in chronically hypoxic newborn lambs.
Keywords: neonatal pulmonary hypertension; hypoxia; high altitude; 2-apb; store operated channels